Network Capital of Youth Organizations Leaders - Anna L. Burmakina (Виртуальная коммуникация и социальные сети)
Network capital provides leaders of youth organizations with mobility. According to P. Bourdieu and J. Urry, network capital develops and maintains social relations without reference to geographical location, which makes it a source of emotional, financial, or practical benefits. Network capital is supplemented and enhanced by digital capital, i.e., digital skills, online activities, membership in virtual communities, etc. Youth organization leaders accumulate network and digital capital at different stages of their career in a youth organization: before joining, as a member, and after leaving. The author interviewed experts and analyzed biographies of youth organization leaders to prove that membership in such organizations provided them with numerous opportunities and accelerated their career. In general, network interactions manifested at different stages of leaders' life path, contributing to their mobility.